2015
DOI: 10.1111/ajco.12438
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic artery embolization in advanced neuroendocrine tumors: Efficacy and long‐term outcomes

Abstract: TAE/TACE are beneficial treatments for control of symptoms as well as tumor growth, with acceptable morbidity and mortality rates. No significant efficacy and survival differences were shown between TAE and TACE. Posttreatment CgA levels and the concurrent use of SSAs were independently associated with survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 40 publications
2
52
0
1
Order By: Relevance
“…targeted agents are used for cases with a moderate tumor burden and/or slow-growing tumors, and cytotoxic chemotherapeutic agents are used for cases with a high tumor burden and/or aggressive tumors. Numerous studies have reported the efficacy and safety of TA(C)E in patients with NETs presenting with liver metastasis [11][12][13][14][15][16][17][18][19] , however, there have been no randomized controlled trials to confirm the survival benefit of TA(C)E, and the positioning of TA(C)E in the treatment of NETs has not yet been clarified in guidelines [20][21][22] . In the current study, the response rate was 56% and the disease control rate was 96%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…targeted agents are used for cases with a moderate tumor burden and/or slow-growing tumors, and cytotoxic chemotherapeutic agents are used for cases with a high tumor burden and/or aggressive tumors. Numerous studies have reported the efficacy and safety of TA(C)E in patients with NETs presenting with liver metastasis [11][12][13][14][15][16][17][18][19] , however, there have been no randomized controlled trials to confirm the survival benefit of TA(C)E, and the positioning of TA(C)E in the treatment of NETs has not yet been clarified in guidelines [20][21][22] . In the current study, the response rate was 56% and the disease control rate was 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Reported median time to progression (TTP)/PFS and median OS from previous studies are 4-36 and 9-80 months, respectively [11][12][13][14][15][16][17][18][19] ( Table 6 ). TTF in this study was comparable to previous reports, while OS was more favorable compared to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been particularly considered in patients with hepatic symptoms or refractory malignant F-NET syndromes[17, 20, 21, •22, 68, 71]. In general TACE/TAE result in a symptomatic response in 50–100% of patients and numerous series as well as case reports have documented their control of symptoms in patients with both carcinoid syndrome and F-pNET syndromes[17, 20, 21, •22, 68, 71, 72, •73, 74, 75, •76, 77, •78]. …”
Section: Summary Of Recent Advances/controversies In Management Ofmentioning
confidence: 99%
“…Both studies and case reports have reported the successful use in patients with carcinoid syndrome of the control of the symptoms of the hormone-excess state by using: everolimus[•38]; PRRT[•56, 57, 66, 95, •96, •148]; liver-directed therapies including TACE/TAE[70, 72, •73, 77, 95, 98, 149]; radioembolization[70, 150, 151]; RFA[80, 81, 83, 95, 152]; by increasing the dosage of octreotide/Lanreotide in refractory cases[94, 97, 153–155]; use of cytoreductive surgery[23, 95, 156–160]; use of 131 I-MIBG[95, 105, 106, 108, 110, •161, 162164]; with the use of the tryptophan hydroxylase inhibitor, Telotristat[108, 113, 114, ••116, •117, 118, 119] and with pasireotide in octreotide resistant cases[•122]. …”
Section: Summary Of Recent Advances In Management Of Specific Hormmentioning
confidence: 99%
“…Установлено, что эффективность их применения зависит от степени злокачественности НЭО, количества и размера метастатических очагов, объема опухолевого поражения печени [25]. Большинство исследователей [26] сходятся во мнении об отсутствии достоверных различий применения ХЭПА и ЭПА, что ставит под сомнение необходимость рутиного использования цитостатических препаратов у больных c НЭО с низким потенциалом злокачественности. По-прежнему отсутствует единое мнение исследователей о сроках начала, кратности и оптимальной методике эндоваскулярных вмешательств.…”
Section: оригинальные статьиunclassified